The Evolution and Variety of RFamide-Type Neuropeptides: Insights from Deuterostomian Invertebrates - Elphick, Maurice R.; Mirabeau, Olivier (Frontiers in Endocrinology, 2014)
Five families of neuropeptides that have a C-terminal RFamide motif have been identified in vertebrates: 1. gonadotropin-inhibitory hormone (GnIH), 2. neuropeptide FF (NPFF) 3. pyroglutamylated RFamide peptide (QRFP), 4. prolactin-releasing peptide (PrRP) and 5. Kisspeptin. Experimental demonstration of neuropeptide-receptor pairings combined with comprehensive analysis of genomic and/or transcriptomic sequence data indicate that, with the exception of the deuterostomian PrRP system, the evolutionary origins of these neuropeptides can be traced back to the common ancestor of bilaterians. Here we review the occurrence of homologs of vertebrate RFamide-type neuropeptides and their receptors in deuterostomian invertebrates - urochordates, cephalochordates, hemichordates and echinoderms. Extending analysis of the occurrence of the RFamide motif in other bilaterian neuropeptide families reveals RFamide-type peptides that have acquired modified C-terminal characteristics in the vertebrate lineage (e.g. NPY/NPF), neuropeptide families where the RFamide motif is unique to protostomian members (e.g. CCK/sulfakinins) and RFamide-type peptides that have been lost in the vertebrate lineage (e.g. luqins). Furthermore, the RFamide motif is also a feature of neuropeptide families with a more restricted phylogenetic distribution (e.g. the prototypical FMRFamide-related neuropeptides in protostomes). Thus, the RFamide motif is both an ancient and a convergent feature of neuropeptides, with conservation, acquisition or loss of this motif occurring in different branches of the animal kingdom.